Research on architecture of novel programmable networks for 6G - Xuliang WANG; Shuo QUAN; Zengyi LIU; Jun ZHANG (Dianxin kexue)
Starting from the industry’s various business scenarios for 6G networks, and the dynamic network capability adjustment requirements for 6G network equipment were deeply analyzed.A programmable network platform architecture with the characteristics of closed-loop self-optimization based on network state management was proposed.Through this architecture design, the existing technology systems related to SDN, NFV, and network AI can be maximized and network administrators can perform network lifecycle management based on network status statements.This platform can provide a new technical realization idea and method for the digital twin network and on-demand network in the future.